Left ventricular mass and myocardial scarring in women with hypertensive disorders of pregnancy. Issue 2 (6th August 2020) - Quesada, Odayme; Park, Ki; Wei, Janet; Handberg, Eileen; Shufelt, Chrisandra; Minissian, Margo; Cook-Wiens, Galen; Zarrini, Parham; Pacheco, Christine; Tamarappoo, Balaji; Thomson, Louise E J; Berman, Daniel S; et al.
Abstract : Aims: Hypertensive disorders of pregnancy (HDP) predict future cardiovascular events. We aim to investigate relations between HDP history and subsequent hypertension (HTN), myocardial structure and function, and late gadolinium enhancement (LGE) scar. Methods and results: We evaluated a prospective cohort of women with suspected ischaemia with no obstructive coronary artery disease (INOCA) who underwent stress/rest cardiac magnetic resonance imaging (cMRI) with LGE in the Women's Ischemia Syndrome Evaluation-Coronary Vascular Dysfunction study. Self-reported history of pregnancy and HDP (gestational HTN, pre-eclampsia, toxaemia and eclampsia) were collected at enrollment. In our cohort of 346, 20% of women report a history of HDP. HDP history was associated with 3.2-fold increased odds of HTN. Women with a history of both HDP and HTN had higher cMRI measured left ventricular (LV) mass compared with women with HDP only (99.4±2.6 g vs 87.7±3.2 g, p=0.02). While we found a similar frequency of LGE scar, we observed a trend towards increased LGE scar size (5.1±3.4 g vs 8.0±3.4 g, p=0.09) among the women with HDP history compared to women without. Conclusion: In a high-risk cohort of women with suspected INOCA, 20% had a history of HDP. Women with HDP history were more likely to develop HTN. Our study demonstrates higher LV mass in women with HDP and concomitant HTN. Although the presence of LGE scar was not different in women with and without HDP history, we observed a trend towards larger scar size in women with HDP. Future studies are needed to better assess the relationship of HDP and cardiac morphology and LGE scarring in a larger cohort of women.